Pendidikan IPS dalam Membentuk Karakter Religius - Anggita (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2023)
Social Sciences (IPS) is a science that covers humans in their social context or humans as cultural and democratic members of society. Social Sciences is a subject that is integrated from social sciences and humanity. In other words, social studies education aims to explore the potential of students to become human beings who are not only knowledgeable, critical, independent but also have noble morals. The objectives of social studies education are in line with the objectives of religious character education. The aim of religious character education is to direct students to have noble character which is reflected in an attitude of faith in God Almighty, so that they behave and speak according to the guidance of the religion they adhere to. Therefore, social studies education plays an important role in shaping the religious character of the nation's children. The religious character values formed through social studies education include three relationships at once, namely the relationship between the individual and God, the individual with others, and the individual with the surrounding environment.